2012
DOI: 10.1371/journal.pone.0052569
|View full text |Cite
|
Sign up to set email alerts
|

Detraining Differentially Preserved Beneficial Effects of Exercise on Hypertension: Effects on Blood Pressure, Cardiac Function, Brain Inflammatory Cytokines and Oxidative Stress

Abstract: AimsThis study sought to investigate the effects of physical detraining on blood pressure (BP) and cardiac morphology and function in hypertension, and on pro- and anti-inflammatory cytokines (PICs and AIC) and oxidative stress within the brain of hypertensive rats.Methods and ResultsHypertension was induced in male Sprague-Dawley rats by delivering AngiotensinII for 42 days using implanted osmotic minipumps. Rats were randomized into sedentary, trained, and detrained groups. Trained rats underwent moderate-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 49 publications
2
42
0
2
Order By: Relevance
“…ITP has characteristics of an immune disease [19][20][21]. Increased oxidative stress is thought to have a role in the pathogenesis of autoimmune disorders because of its contribution to inflammation and its role in apoptotic cell death, in addition to decreasing immune system functions [22]. Zhang et al reported that gene expression and molecular-oxidative stress presented as causative factors for chronic ITP in children [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…ITP has characteristics of an immune disease [19][20][21]. Increased oxidative stress is thought to have a role in the pathogenesis of autoimmune disorders because of its contribution to inflammation and its role in apoptotic cell death, in addition to decreasing immune system functions [22]. Zhang et al reported that gene expression and molecular-oxidative stress presented as causative factors for chronic ITP in children [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also reported that a 3-week intervention with low-fat, high-fiber diet combined with low-intensity CVE training induced a remarkable improvement in blood pressure, oxidative stress and NO availability, in hypertensive patients [97]. Likewise, Agarwal et al [98] reported that 4 weeks of moderate-intensity CVE training in hypertensive rats not only reduced blood pressure and improved cardiac function but also reduced inflammatory cytokines and norepinephrine, diminished activation of NF-κB and decreased oxidative stress, as indicated by the reduction in inducible nitric oxide synthase (iNOS) expression and the increased levels of cooper/zinc containing superoxide dismutase (Cu/ZnSOD) within the paraventricular nucleus (PVN). PVN is a crucial brain region that serves as an autonomic control center regulating cardiovascular, neuroendocrine and physiological functions [99,100].…”
Section: Effect Of Exercise On Hypertension and Oxidative Stressmentioning
confidence: 85%
“…However, the current study shows that spatial behavior after a running program may be a reflection of a decrease in stress or an increase in self-control and confidence. The effect of physical activity on emotional state has been mainly measured using laboratory parameters such as chemical changes in saliva, cortisol [21], blood levels of serotonin and norepinephrine, using physiological parameters of blood pressure, heart rate, cholesterol, oxidative stress and free radicals [22], or using behavioral factors such as sleeping and eating [23][24]. However, increase in movement in aged rodents following an exercise program as an indication of decreased anxiety, stress and self-confidence has not documented.…”
Section: Discussionmentioning
confidence: 99%